Policy Analysis Responsive to Gender Equality in Makassar City - Roslianah, Roslianah (Institut Pemerintahan Dalam Negeri Kampus Sulawesi Selatan, 2024)
The aim of this research is to determine the extent to which public policy responds to interests in gender equality. The research method used is qualitative, with data sourced from specific community groups by analyzing women’s involvement in various aspects. Data was analyzed using qualitative methods, including data reduction, data display, and data verification. The research results show that Gender Mainstreaming (PUG) development carried out through related department guidance has shown progress, although it has not run optimally. Meanwhile, in social relations manifested in economic life, politics, legal order, and human rights values, we see how women are active in various areas. Several Human Development Index (HDI) components are used as benchmarks, especially in women’s empowerment, and research results show an increase, particularly in the role of women in parliament, which influences women's roles in other sectors. However, with these improvements, government commitment and consistency are needed, especially in budget availability and the extent to which strategic programs are communicated, which do not appear to be running as they should.